The Right of the Indigenous People over Their Natural Resources: The Nigeria Situation - Adams Adoga-Ikong; Patience Tah Besong (PREDESTINASI, 2021)
One burning issue in Nigeria today especially around the oil producing areas is that of the absolute ownership and control of the natural resources (oil) that God has endowed the people with. In the last thirty years if not more, the agitation has become more fiece from demand for self-determination, in the 60s to Kiama declaration in the 70s and recently to resource control. Every successive government in the country has come out with policies to calm the situation and even to ameliorate the hardship suffered by the people due to the negative effects of the exploitation of the oil mineral and other natural resources. Despite the above, the agitations are still on going. These come with various conferences, workshops, seminars symposia and radio and television talks on this issue by many stakeholders in Nigeria. Some of these agitations have become violent and various other crimes in the country. The various agitations are predicted on the right of the people to own and control (their) natural resources. The question then is, who are these indigenous people?What are their rights over the natural resources in their domain? What does Nigerian legislation say about the natural resources found beneath the earth in the country? And what will be the way forward?